Uso de dados para tomada de decisão estratégica em adquirentes no Brasil - Haddad, Rodrigo Santos (Universidade Federal de São Carlos, 2025)
Data intelligence, through technologies such as Big Data, can generate competitive advantage in a highly concentrated and competitive market. Therefore, the present study aims to analyze the use of data in strategic decision- making within the acquiring sector in Brazil. Based on a qualitative approach and employing the case study method, interviews were conducted with professionals working in one of the major acquiring companies in the country, seeking to identify the role of data in strategy formulation. The research demonstrates that companies in this specific industry, when able to capture, integrate, and interpret relevant data, have a greater ability to adjust their strategies in real time, optimizing resources and expanding their market share. The analysis also highlights the transition from a consolidated duopoly to a more fragmented scenario, driven by cost-focused and differentiation strategies or a combination of both supported by timely analytical insights. The study concludes that the structured and strategic use of data is a determining factor for competitiveness in the Brazilian acquiring sector, especially in volatile contexts such as those observed during and after the pandemic.
Use of data for strategic decision making in acquirers in Brazil
Keywords: Tomada de decisão; Big Data; Inteligência de negócios; Estratégia competitiva; Mercado de adquirentes; Decision-making; Big Data; Business intelligence; Competitive strategy; Acquiring market; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO